Publications récentes (Relations Industrielles / Industrial Relations, 2003)
This article presents recent publications on industrial relations. Some of the publications include "Evolution of the Model of Industrial Relations in Bulgaria 1989-2002," by Teodor Detchev, "Labor Contract Negotiations in the Airline Industry," by Andrew von Nordenflycht and Thomas A. Kochan, "Collective Bargaining and Staff Salaries in American Colleges and Universities," by Daniel B. Klaff and Ronald G. Ehrenberg, and "Final-Offer Arbitration: A New Zealand Variation," by Ian McAndrew.
Keywords: Human capital; Industrial relations; LABOR arbitration; LABOR laws & legislation; Labor contracts; Labor economics